An Empirical Study on Random Walk and Market Efficiency in London Stock Exchange under Normal Period and Crisis Period - Feng, Li (2013)
This paper examines random walk hypothesis for daily data of FTSE 100 index. Conforming to random walk hypothesis implies weak form market efficiency. Observation period starts on 2nd April of 1984 and terminates on 28th Mar of 2013. By dividing observation period into normal period, 2008 global financial crisis period and entire observation period, this paper detects random walk behavior of return series and hence market efficiency of London Stock Exchange under different market condition. A part from evidence of higher-order serial correlation within return series, London Stock Exchange is weak form efficient under crisis period. However, weak form efficiency under normal period is rejected. For the entire observation period, higher-order serial correlation is also observed; while other empirical results support weak form efficiency of London Stock Exchange. Overall, this study argues market efficiency of London Stock Exchange does vary under different market condition. Moreover, market efficiency has improved during 2008 global financial crisis.